O SUBALTERNO NAS NARRATIVAS LITERÁRIAS DO SUL GLOBAL: Testemunhos, margens e marginalizados nas obras de Paulo Lins e Evel Rocha - OLIVEIRA, Igor Luid de Souza (2024)
This study aims to compare the novels Cidade de Deus (1997) and Marginais (2010), both narratives from the Global South, respectively written in Brazil and Cape Verde, in order to identify similarities and differences in the representation of subaltern subjects, peripheries, and violence. Although the novels operate in distinct literary spaces, they both play a significant role today in addressing discourses, testimonies, and forms of social denunciation (SeligmannSilva 2005, Junior 2010). Methodologically, the research is primarily based on comparative studies (Carvalhal, 2006) and seeks to explore the intersections between personal biographies, modes of constructing fictional narratives, and life experiences to discuss the conditions of speech for previously silenced subjects in the Global South. The theoretical foundation of the research is supported by two main blocks: the literature of testimony in Latin America, which investigates the intersections between representations, violence, and literary forms (Marco, 2004, Bosi, 1995), and the perspectives offered by cultural studies and postcolonial theories from a post- colonial and comparative context (Santiago, 2000). In this way, thinking about this research will result in contributions to the field of literatures that belong to the global south, presenting how these literatures are in dialogue on various themes, contexts, characters and experiences.